The Salman Mosque: The Pioneer of the Mosque Design Idea, the Driving Force Behind the Coinage of the Term ‘Campus Mosque’ in Indonesia - Dewiyanti, Dhini; Budi, Bambang Setia (Journal of Islamic Architecture, 2015)
This article is a part of a journey to understand the existential meaning of the Salman Mosque. One of the topics to be raised is the knowledge that the Salman mosque is capable of becoming a reformer in various fields. The focus of discussion is on the design idea and the Salman Mosque as the pioneer for coinage of the term ‘campus mosque’ in Indonesia. The design of the Salman Mosque that brought about a radical change in its beginning, established the Salman mosque as reformer. Through the qualitative approach conducted between 2011 until 2015, information was obtained through explorative interviews with the mosque architects: Achmad Noeman and those involved with the daily activities of the mosque such as: management, members of mosque units and divisions, residents of the mosque dormitory and prominent figures of society. This assessment is expected to be able to provide knowledge on the Salman mosque especially as it is associated with the term ‘campus mosque’.